2015
DOI: 10.7185/geochemlet.1502
|View full text |Cite
|
Sign up to set email alerts
|

Rapid response of silicate weathering rates to climate change in the Himalaya

Abstract: 11(<100 yr) to climate change and may act as a key component in the atmospheric CO 2 level short-term regulation (Beaulieu et al., 2012). However, the relative role of climatic parameters on chemical weathering is still debated. Model simulations and geochemical studies of river-born material highlight either a temperature dependence (Walker et al., 1981), where warming promotes chemical weathering, or a predominance of other parameters like mechanical erosion (Raymo and Ruddiman, 1992;Gaillardet et al., 1999;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 30 publications
2
22
0
Order By: Relevance
“…Compared to dominant silicate rocks that outcrop in the Nile Basin (see Fig. S4), clays are preferentially enriched in 6 Li, as expected for secondary phases formed on continents7. The particular behavior for Li isotopes during arid versus humid periods is consistent with K/Ti and Mg/Ti variations, reflecting mitigated effects of leaching processes in weathering profiles, which release dissolved Li to the surrounding waters, and clay neoformation, which immobilizes Li (and Mg) in specific soil horizons37.…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…Compared to dominant silicate rocks that outcrop in the Nile Basin (see Fig. S4), clays are preferentially enriched in 6 Li, as expected for secondary phases formed on continents7. The particular behavior for Li isotopes during arid versus humid periods is consistent with K/Ti and Mg/Ti variations, reflecting mitigated effects of leaching processes in weathering profiles, which release dissolved Li to the surrounding waters, and clay neoformation, which immobilizes Li (and Mg) in specific soil horizons37.…”
mentioning
confidence: 59%
“…In contrast, experimental and field studies have demonstrated significant fractionation of Li isotopes during silicate weathering, with preferential incorporation of 6 Li in neoformed clay minerals25. Recent works illustrate the potential of δ 7 Li (δ 7 Li = ( 7 Li/ 6 Li) sample /( 7 Li/ 6 Li) LSVEC ) − 1) × 1000) as a proxy for determining the intensity or the regime of chemical weathering726. Li in river waters and particles is essentially derived from alteration of silicate lithologies2728.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, significant debates still exist on possible links between global climate change and the India-Asia continent collision (Kerrick and Caldeira, 1999;Willenbring et al, 2013), because silicate weathering in response to plateau uplift sequesters carbon (Raymo and Ruddiman, 1992;Dosseto et al, 2015), whereas syn-collisional volcanism (e.g. Mo et al, 2008;Niu et al, 2013;Zhu et al, 2015), post-collisional volcanism (Guo et al, 2006(Guo et al, , 2007(Guo et al, , 2013(Guo et al, , 2014a(Guo et al, , 2015a, subduction zone metamorphism (Kerrick and Connolly, 2001;Cook-Kollars et al, 2014) and modern hydrothermal activities (Guo et al, 2014b;Zhang et al, 2014Zhang et al, , 2016 release carbon.…”
Section: Introductionmentioning
confidence: 98%
“…Due to the heavy monsoonal rainfall with strong physical erosion intensity, smectite is washed away from rock surfaces shortly after its formation, preventing it from continuous chemical weathering toward halloysite and kaolinite. In particular, recent studies have demonstrated that chemical weathering rate can respond rapidly to decade-to millennial-scale climate changes with rainfall and temperature variations (e.g., Beaulieu et al, 2012;Dosseto et al, 2015;Gislason et al, 2009). In particular, recent studies have demonstrated that chemical weathering rate can respond rapidly to decade-to millennial-scale climate changes with rainfall and temperature variations (e.g., Beaulieu et al, 2012;Dosseto et al, 2015;Gislason et al, 2009).…”
Section: Clay Mineral Variations Associating With the East Asian Summmentioning
confidence: 99%